ANALISIS KONSEPTUAL ETIKA PROFESI GURU DALAM PERSPEKTIF PENDIDIKAN ISLAM - Pangesti Hidayah; Umi Rokhyatul Mualifah; Sabriani Zahwa Syafitri; Nur Khasanah (STKIP Subang, 2026)
ABSTRACT Teacher professional ethics in Islam play an important role in determining the quality of education that focuses on intellectual development as well as students' spirituality and character. In the contemporary era, the development of digital technology has brought various changes to the world of education which have influenced student behavior and demanded the strengthening of ethical values ​​in the teaching profession. This research uses a qualitative method with a library research approach through analysis of various relevant literature sources in the form of books, scientific journals and previous research. The research results show that teacher professional ethics from an Islamic education perspective can be understood as a set of values ​​that serve as guidelines for carrying out teaching duties. which emphasizes the values ​​of sincerity, example and honesty as the main basis for carrying out the teaching profession. Apart from that, this research also emphasizes the various challenges faced in implementing professional ethics for teachers in the digital era, such as changes in the character of students, generation gaps, and the complexity of teacher workload. Keywords: Ethics, Islamic Education, Professional Ethics of Teachers ABSTRAK Etika profesi guru dalam Islam memainkan peran penting dalam menentukan kualitas pendidikan yang berfokus pada pembangunan intelektual serta spiritualitas dan karakter siswa. Dalam era kontemporer, perkembangan teknologi digital membawa berbagai perubahan dalam dunia pendidikan yang turut memengaruhi perilaku peserta didik dan menuntut penguatan nilai-nilai etika dalam profesi keguruan. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan (library research) melalui analisis berbagai sumber literatur yang relevan berupa buku, jurnal ilmiah, dan penelitian terdahulu. Hasil penelitian menunjukkan bahwa etika profesi guru dalam perspektif pendidikan islam dapat dipahami sebagai seperangkat nilai yang menjadi pedoman dalam menjalankan tugas keguruan. yang menekankan nilai keikhlasan, keteladanan, dan kejujuran sebagai dasar utama dalam menjalankan profesi guru. Selain itu, penelitian ini juga menekankan pada berbagai tantangan yang dihadapi dalam penerapan etika profesi guru di era digital, seperti perubahan karakter peserta didik, kesenjangan generasi, serta kompleksitas beban kerja guru. Kata Kunci: Etika, Pendidikan Islam, Etika Profesi guru